Microsoft SQL server 2008 [ new features - Otey, Michael , 1958- (McGraw Hill, 2009)
Offers details on the innovative features and benefits available in SQL Server 2008. This guide provides an overview of the enterprise data management capabilities, developer functions, Business Intelligence tools, and security enhancements. It is suitable for decision-makers, developers, and DBAs preparing for upgrades or migration